Estimating the Position of an Image with Unknown Intensity Shape - Yury E. Korchagin; Viacheslav N. Vereshchagin; Alexander V. Terekhov; Kirill A. Melnikov (Communications - Scientific letters of the University of Zilina, 2021)
The problem considered is to estimate the image position of a spatially extended object. It is assumed that the shape of the image intensity is a priori unknown, but it can be predicted with some error. In order to synthesize the estimate of the image position, the quasi-likelihood version of the maximum likelihood method is used. Behavior of the signal function in the neighborhood of the real image position is studied. Characteristics of the resulting estimate, such as bias and dispersion, are found by means of the local Markov approximation method. Influence of non-uniformity of the received image intensity upon the estimate accuracy is demonstrated by an example of receiving the rectangular image with linearly varying intensity.